Recurrent Unprovoked Venous Thromboembolism in a Young Female Patient with High Levels of Homocysteine - Sule, Ashish Anil; Chin, Tay Jam; Khien, Lee Hwei (International Journal of Angiology, 2012)
Hyperhomocysteinemia is a rare condition which predisposes to atherothrombosis. Recurrent venous thromboembolism (VTE) with hyperhomocysteinemia is known but extremely uncommon. Homocysteine levels of more than 22 umol/L can predispose to VTE in a middle-aged women. We describe a case of a middle-aged woman, community ambulant with recurrent VTE with intermediately high homocysteine levels. She had no other risk factors for recurrent venous thrombosis. In our article, we also discuss hyperhomocysteinemia and its link to VTE.
Keywords: antifactor Xa; cardiovascular risk factors; deep vein thrombosis; factor V Leiden; hypertension; thrombophilia